The determinants of financial ratio disclosures and quality: Australian evidence - Aripin, Norhani (Curtin University, 2010)
This thesis seeks to explain the extent and quality of financial ratio disclosures within the 2007 annual reports of 300 Australian listed firms. Agency theory is utilised as the underlying theoretical framework. The extent of financial ratio disclosures (EFRD) is captured through a 43-item financial ratio disclosures index. A 12- item qualitative matrix using the IASB Conceptual Framework is created measuring the quality of financial ratio disclosures (QFRD).The findings reveal that the EFRD of sample firms is 5.3%. Share Market Measures, Capital Structure and Profitability are slightly more popular ratios (still below 10%) with virtually no communication of the Liquidity and Cash Flow sub-categories. The QFRD disclosure is 37.8%. Reliability and Understandability are better handled, followed by Comparability and Relevance qualitative characteristics.Regression analysis indicates firm size and ownership concentration are statistically significant predictors of EFRD. Larger firms with greater disperse ownership structure disclose financial ratios more extensively than their smaller counterparts. Larger firms also provide more qualitative information supporting the use of financial ratios. Better corporate governance structures and greater capital management initiatives do not appear to explain the extent or quality of financial ratio disclosures.These thesis findings have important implications for understanding managerial communication incentives as they relate to the extent and quality of financial ratio disclosures within the annual reports of ASX listed firms. One key policy implication is that financial ratio disclosures are a valuable tool highlighting major financial and operational characteristics of firms. Small firms and those firms with less concentrated ownership structures should consider allocating further resources in disclosing financial ratio information. Accounting policy makers can reasonably target loss making firms and non-Big4 clients with the view of providing mechanisms to enhance financial ratio disclosures. Such moves are desirable since accountability, transparency and adherence to corporate governance attributes would likely be enhanced.